Malaysian politics under Mahathir - Milne, R. S. (Robert Stephen) 1919-; Mauzy, Diane K. 1942- (Politics in Asia series, 1999)
A hard-hitting and readable book which examines Mahathir's character, his ideas and policies and relates them to the social, economic and political setting inside Malaysia. Up until recently, high rates of economic growth and a striking reduction in poverty have been the hallmarks of this vibrant Tiger economy. Mahathir's success has now been placed in jeopardy by the recent economic crisis, and his rule is coming under hostile scrutiny. As one of the most controversial political figures in South-east Asia, Mahathir's success at managing ethnic tensions, policies of industrialization, modernization and foreign policy are explored, as are his grandiose projects, his human rights record and approach to corruption. Milne and Mauzy, leading authors in this field, assess Mahathir's rule within this context as well as the abrupt dismissal from office, arrest and trial of Anwar Ibrahim, Mahathir's deputy, in late 1998.